Scanning tunneling microscopy and Raman spectroscopy of polymeric sp–sp2 carbon atomic wires synthesized on the Au(111) surface. Issue 39 (27th September 2019) - Rabia, Andi; Tumino, Francesco; Milani, Alberto; Russo, Valeria; Li Bassi, Andrea; Achilli, Simona; Fratesi, Guido; Onida, Giovanni; Manini, Nicola; Sun, Qiang; Xu, Wei; Casari, Carlo S.
Abstract : The structure and electronic and vibrational properties of sp–sp 2 carbon atomic wires have been investigated by combined STM/STS and Raman spectroscopy. Abstract : Long linear carbon nanostructures based on sp-hybridization can be synthesized by exploiting on-surface synthesis of halogenated precursors evaporated on Au(111), thus opening a way to investigations by surface-science techniques. By means of an experimental approach combining scanning tunneling microscopy and spectroscopy (STM and STS) with ex situ Raman spectroscopy we investigate the structural, electronic and vibrational properties of polymeric sp–sp 2 carbon atomic wires composed by sp-carbon chains connected through phenyl groups. Density-functional-theory (DFT) calculations of the structure and the electronic density of states allow us to simulate STM images and to compute Raman spectra. The comparison of experimental data with DFT simulations unveil the properties and the formation stages as a function of the annealing temperature. Atomic-scale structural information from STM complement the Raman sensitivity to the single molecular bond to open the way to detailed understanding of these novel carbon nanostructures.